Students' Discipline in learning physics lesson: A study in San Roque National High School, Gapan City - Sienna G. Magno (Cahaya Ilmu Cendekia Publisher, 2020)
Purpose of the study: This research aims to explore the discipline of students in learning science, especially physics lesson in grade 7, San Roque National High School. Methodology: This research is a mixed research, which combines quantitative and qualitative approaches. The quantitative is shown by descriptive statistical data, while the qualitative is shown by the results of the interview. The sample of this study was 7th grade students at San Roque National High School. Main Findings: The results in this study indicate that the majority of students have a fairly good discipline attitude in learning science, as indicated by the results of descriptive statistics, which shows as many as 38.1% of students have fair independence. The remaining 4.1% of students are categorized as very low, 21.6% of students are categorized as low, 26.8% are categorized as high, and 9.3 students are categorized as very high. Applications of this study: This research is very useful for science teachers, especially physics teacher in identifying and knowing the descriptive of students' discipline attitude in learning physics lesson, especially in the Philippines. Novelty/Originality of this study: This research only focuses on looking at the students' discipline attitude in learning physics lesson, at San Roque National High School, especially grade 7.